Planning education: exchanging approaches to teaching practice-based skills. Issue 1 (2nd January 2017) - Ritchie, Heather; Sheppard, Adam; Croft, Nick; Peel, Deborah
Abstract: Planning curricula have continually evolved to meet changing societal needs, technological change and employer expectations. The professional accrediting body in the United Kingdom, the Royal Town Planning Institute, stipulates the core planning skills required, differentiating between formal classroom-based learning and professional competencies, derived in practice. Previous research identified the need to address perceived inadequacies in graduate planners' practical skills, such as decision-making, leadership, and communication, including negotiating, influencing and using evidence. Emphasis has also been placed on planning schools sharing innovative practice to improve student learning. This paper critically reflects on the challenges of teaching diverse cohorts and presents the findings from a sponsored teaching exchange research programme. Case studies drawn from each institution are used to illustrate practice-orientated planning education approaches in the classroom to better equip students for the workplace.